2015
DOI: 10.1155/2015/121925
|View full text |Cite
|
Sign up to set email alerts
|

Choline and Cystine Deficient Diets in Animal Models with Hepatocellular Injury: Evaluation of Oxidative Stress and Expression of RAGE, TNF-α, and IL-1β

Abstract: This study aims to evaluate the effects of diets deficient in choline and/or cystine on hepatocellular injury in animal models (young male Wistar rats, aged 21 days), by monitoring some of the oxidative stress biomarkers and the expression of RAGE, TNF-α, and IL-1β. The animals were divided into 6 groups (n = 10) and submitted to different diets over 30 days: AIN-93 diet (standard, St), AIN-93 choline deficient (CD) diet and AIN-93 choline and cystine deficient (CCD) diet, in the pellet (pl) and powder (pw) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 68 publications
(86 reference statements)
1
10
0
Order By: Relevance
“…Moreover, the liver may be injured during the course of many diseases that are systemic or predominantly involve other organs, as sepsis, cardiovascular diseases (CVD), obesity, chronic kidney disease (CKD) and diabetes [ 35 ]. Despite the large number and variety of initiating factors, derived from extra- or intrahepatic environments [ 25 , 35 , 36 ], the final results are restricted, including death of hepatocytes or cholangiocytes leading, in severe cases, to the stereotyped anatomical and clinical patterns of portal hypertension, with or without cirrhosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the liver may be injured during the course of many diseases that are systemic or predominantly involve other organs, as sepsis, cardiovascular diseases (CVD), obesity, chronic kidney disease (CKD) and diabetes [ 35 ]. Despite the large number and variety of initiating factors, derived from extra- or intrahepatic environments [ 25 , 35 , 36 ], the final results are restricted, including death of hepatocytes or cholangiocytes leading, in severe cases, to the stereotyped anatomical and clinical patterns of portal hypertension, with or without cirrhosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In nonruminant species, the essential role of choline and Met to prevent lipidosis has been demonstrated and feeding choline-and Met-deficient diets is a common methodology to induce hepatic steatosis and lipidosis 5,6 . Deficiencies in these lipotropic nutrients may also contribute to lipidosis in ruminants 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Choline supplements were also observed to lower exercise-induced lipid peroxidation and increase serum Vitamin A and E levels in women [47]. In turn, studies show that dietary deficiency of choline increases hydrogen peroxide production in liver mitochondria by causing lipid peroxidation of hepatocytes [48]. DHA is another supplement used in this study whose high levels in brain tissue have been shown to decrease brain lipid peroxidation [59] and when supplemented as combined eicosapentaenoic acid-docosahexaenoic it decreases lipid peroxidation and increases antioxidant enzyme activity in brain of hypercholesterolemic rats [52].…”
Section: Discussionmentioning
confidence: 96%
“…Administration of choline to women caused decrease in oxidative stress levels [47]. Dietary deficiency of choline increases lipid peroxidation in hepatocellular cells [48] and apoptosis in the foetal brain [9,60]. Similarly, docosahexaenoic acid (DHA) is another essential dietary nutrient.…”
Section: Introductionmentioning
confidence: 99%